2016
DOI: 10.1007/s10237-016-0837-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel constitutive model for passive right ventricular myocardium: evidence for myofiber–collagen fiber mechanical coupling

Abstract: The function of right ventricle (RV) is recognized to play a key role in the development of many cardiopulmonary disorders, such as pulmonary arterial hypertension (PAH). Given the strong link between tissue structure and mechanical behavior, there remains a need for a myocardial constitutive model that accurately accounts for right ventricular myocardium architecture. Moreover, most available myocardial constitutive models approach myocardium at the length scale of mean fiber orientation, and do not explicitl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 52 publications
6
59
0
1
Order By: Relevance
“…5 and 6 and compare the low-strain regime responses; note that the longitudinal direction is nearly aligned with the mean myofiber direction.) Comparisons of the measured volume fraction and estimated values of myofiber stiffness (Table I) with corresponding values for normal tissues 20 further indicated that the myofiber stiffening stems primarily from an increase in the stiffness of myofibers (increased by ~75%), and secondarily from an increase in volume fraction of these fibers (increased by ~16%). In this connection, we recall from our experimental study 14 that the myofiber mass increased more than its volume leading to an ~40% increase to myofiber density.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…5 and 6 and compare the low-strain regime responses; note that the longitudinal direction is nearly aligned with the mean myofiber direction.) Comparisons of the measured volume fraction and estimated values of myofiber stiffness (Table I) with corresponding values for normal tissues 20 further indicated that the myofiber stiffening stems primarily from an increase in the stiffness of myofibers (increased by ~75%), and secondarily from an increase in volume fraction of these fibers (increased by ~16%). In this connection, we recall from our experimental study 14 that the myofiber mass increased more than its volume leading to an ~40% increase to myofiber density.…”
Section: Discussionmentioning
confidence: 88%
“…This fraction was estimated to be about 3% for both normal and PAH cases ( ϕ g = 0.03). Next, following the recent approach, 20 we used 3-D Beta distribution functions Γ m ( θ m , z ) and Γ c ( θ c , z ) to present transmural distribution of myo- and collagen fibers orientation, respectively. Here, z denotes the normalized thickness varying between 0 at endocardium to 100 at epicardium along the transmural direction (denoted by x 3 ), and θ m , θ c ∈ [− π /2, π /2] are used to denote the planar orientation of myo- and collagen fibers, respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations